Two-Electron, Two-Proton Oxidation of Catechol: Kinetics and Apparent Catalysis - Lin, Q; Li, Q; Batchelor-McAuley, C; Compton, R (2015)
The study of proton-coupled electron transfer reactions is of great current interest. In this work, the catechol redox process was studied voltammetrically in the pH range from 1.0 to 14.0 using a glassy carbon electrode. Analysis of the peak potentials and currents together with Tafel analysis allowed the inference of the likely transition states and electrode reaction mechanism. Modification of the glassy carbon electrode surface with sparse coverages of alumina particles was shown to lead to strong apparent catalysis of the catechol redox process at low pH. A possible mechanism for this is proposed.